Changing Religiosities in the Nordic Countries : A Complexity Perspective - Andersen, Peter B.,; Gundelach, Peter, (International Studies in Religion and Society ;, 2025)
The book argues that changes in religiosity in the Nordic countries cannot be adequately explained by the dominate all-encompassing generalizations theories of religious change because religious changes are both similar but and diverse in the Nordic countries. For instance, church membership is decreasing in all countries, but the state-church relationship varies. The book argues for the fruitfulness of the Complexity Frame of Reference, a new theoretical framework which is favours a more nuanced analysis of religious change. This is demonstrated in qualitative and quantitative studies of comparative studies and case studies of religious participation, beliefs, rites, and values.